2012
DOI: 10.1039/c2dt30205e
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the formation of UO2(NO3)42− in an ionic liquid by EXAFS

Abstract: The complexation between uranium(vi) and nitrate ions in a hydrophobic ionic liquid (IL), namely [BMI][NO(3)] (BMI = 1-butyl-3-methylimidazolium(+)), is investigated by EXAFS spectroscopy. It was performed by dissolution of uranyl nitrate UO(2)(NO(3))(2)·6H(2)O or UO(2)(Tf(2)N)(2) (Tf(2)N = bis(trifluoromethylsulfonyl)imide (CF(3)SO(2))(2)N(-)). The formation of the complex UO(2)(NO(3))(4)(2-) is evidenced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 40 publications
0
17
1
Order By: Relevance
“…By taking into account of the coordination of water molecules introduced by dissolving UO 2 (NO 3 ) 2 ·6H 2 O in [BMIm][NO 3 ], the specific structure [UO 2 (η 2 ‐NO 3 ) 2 (η 1 ‐NO 3 )(H 2 O)] − was suggested. It was different from the results given by Gaillard et al. By dissolution of a low concentration of UO 2 (NO 3 ) 2 ·6H 2 O or UO 2 (Tf 2 N) 2 in [BMIm][NO 3 ] to keep the [NO 3 − ]/[UO 2 2+ ] ratio equal to 600, they found that the formed complex is UO 2 (NO 3 ) 4 2− and the 1 : 4 nitrato‐complex of uranyl was coordinated with two bidentate and two monodentate nitrate groups to uranyl, that was [UO 2 (η 2 ‐NO 3 ) 2 (η 1 ‐NO 3 ) 2 ] 2− .…”
Section: Determination Of Actinide Speciation By Xafscontrasting
confidence: 71%
“…By taking into account of the coordination of water molecules introduced by dissolving UO 2 (NO 3 ) 2 ·6H 2 O in [BMIm][NO 3 ], the specific structure [UO 2 (η 2 ‐NO 3 ) 2 (η 1 ‐NO 3 )(H 2 O)] − was suggested. It was different from the results given by Gaillard et al. By dissolution of a low concentration of UO 2 (NO 3 ) 2 ·6H 2 O or UO 2 (Tf 2 N) 2 in [BMIm][NO 3 ] to keep the [NO 3 − ]/[UO 2 2+ ] ratio equal to 600, they found that the formed complex is UO 2 (NO 3 ) 4 2− and the 1 : 4 nitrato‐complex of uranyl was coordinated with two bidentate and two monodentate nitrate groups to uranyl, that was [UO 2 (η 2 ‐NO 3 ) 2 (η 1 ‐NO 3 ) 2 ] 2− .…”
Section: Determination Of Actinide Speciation By Xafscontrasting
confidence: 71%
“…The observed anion:copper ratios do not necessarily indicate that the anions are coordinated with the copper, as previous work indicates that charged metal complexes are soluble in ILs [14,15] and uncoordinated ions can move into the IL phase in tandem with a charged metal complex to maintain electroneutrality [59,60]. As indicated in Table 3, all three mineral anions used in the present study coordinate relatively weakly with copper(II).…”
Section: Extractions Involving a Single Copper Saltmentioning
confidence: 53%
“…As a class, ILs are largely non-flammable and non-volatile, potentially simplifying their use in commercial environments [5][6][7]. A more fundamental advantage is that while ionic metal complexes are generally insoluble in organic phases, ILs are capable of solvating ionic as well as neutral metal complexes [14,15]. This amounts to the removal of a constraint on the coordination chemistry underlying extraction, offering researchers greater flexibility in process design.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of nitrate groups bound in ab identate fashion can be evidenced by the shoulder on the FT at R + DR = 2.3-2.4 (from Na toms) andt he peak at R + DR = 3.7 ( from Oa toms). Notably,t his kind of coordination of nitrates to uranium (VI) is predominant, even in ionic liquids, [41,42] and we did not consider am onodentate coordination of nitrates. The monodentate coordination of TBP molecules in the uranyl spherer esults in the presence of Pa toms at R + DR % 3.4 o nt he FT.W ed id not consider any bidentate coordination of TBP as it has never been reported, to our knowledge.…”
Section: Exafs Spectroscopymentioning
confidence: 98%